Beef handling practices at Abattoirs and Butcher shops in Uganda: implications for meat safety and health of consumers - Juliet Kyayesimira; Florence Muheirwe (East African Journal of Biophysical and Computational Sciences)
Proper beef handling contributes to achieving sustainable development goals 3 (good health and well-being) and 12 (sustainable consumption and production patterns). This is because it ensures the safety of meat and consumers’ health. However, the meat sector is still underdeveloped in most African countries. In addition, there is limited research addressing meat safety challenges. In Uganda particularly, in the recent past, there was whistle-blowing over contaminated beef on the market, indicating a  loophole in food safety. Despite this, studies focusing on beef handling practices have remained scanty. Thus, this study aimed to examine beef handling practices at the abattoirs and butcher shops in Uganda's Central, Western, and Eastern regions. A mixed-methods approach was employed to collect data through a survey, in-depth interviews, and on-site observations. Findings revealed that beef handling practices were poor at abattoirs and butcher shops and that most facilities for safety measures were lacking or inadequate. Only 3% of the respondents had cold room storage facilities, and meat spoilage was relatively high (85.3%). Appropriate knowledge of meat safety among abattoir and butcher operators was inadequate, contributing to low compliance with food safety guidelines. Inappropriate handling practices and poor handling facilities may put consumers at a health risk. The study recommends that responsible authorities should ensure compliance mechanisms and sensitization initiatives are prioritized.